2021
DOI: 10.3390/antibiotics10050504
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Cefepime in Adults with Hematological Malignancies and Febrile Neutropenia after Chemotherapy

Abstract: Patients with chemotherapy-induced febrile neutropenia (CIFN) may have changes in the pharmacokinetics (PK) compared to patients without malignancies or neutropenia. Those changes in antibiotic PK could lead to negative outcomes for patients if the therapy is not adequately adjusted to this. In this, open-label, non-randomized, prospective, observational, and descriptive study, a PK model of cefepime was developed for patients with hematological neoplasms and post-chemotherapy febrile neutropenia. This study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The purpose of this mini review was to briefly survey the techniques and decisions researchers made while performing cefepime PTA. Therefore, only the first 20 titles were reviewed, of which 14 met the inclusion criteria of a PTA study, with at least one evaluation of cefepime alone in adult patients ( Table 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. A study by Das et al was excluded because cefepime was studied in combination with a novel beta-lactamase inhibitor, changing the risk benefit from cefepime alone [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The purpose of this mini review was to briefly survey the techniques and decisions researchers made while performing cefepime PTA. Therefore, only the first 20 titles were reviewed, of which 14 met the inclusion criteria of a PTA study, with at least one evaluation of cefepime alone in adult patients ( Table 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. A study by Das et al was excluded because cefepime was studied in combination with a novel beta-lactamase inhibitor, changing the risk benefit from cefepime alone [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…All authors reported a clear purpose for the PTA. Common purposes were to explore optimal doses in a special patient population, explore the success of achieving different PD targets, or exploring the success of one dosing regimen over another [ 14 , 15 , 17 , 18 , 25 ]. The number of virtual patients simulated varied from 1000 to 12,000.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that FEP is often used to treat leukemia patients with combined infections. Compared with other cephalosporins, FEP not only has good stability against β-lactamase produced by bacteria and is less likely to induce resistance, 11 but also has good clinical application prospects in the treatment of ESBLs-positive E. coli infections. At the same time, giving a higher dose of FEP to Gram-negative rods can also achieve ideal therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with those in the nonfebrile neutropenia cohort, the vancomycin concentration/dose ratio was significantly lower, and vancomycin clearance was significantly higher in the febrile neutropenia cohort. Previous studies have indicated that febrile neutropenia alters the pharmacokinetics of several antibiotics, especially beta-lactams, such as cefepime, 24 doripenem, 25 ceftazidime, 26 and piperacillin. 27 In addition, the pharmacokinetics of drugs are dependent on elevated clearance and distribution volume.…”
Section: Discussionmentioning
confidence: 99%